ULOS RAGI HIDUP DENGAN BATIK MOTIF GORGA PADA DESAIN BUSANA PESTA GALA - Sri Purwani; Stephanie Angela R Siburian (Jurnal Socia Akademika, 2022)
This study aims to: 1) determine the combination of Living Yeast Ulos Fabric with Gorga Motif Batik in the Gala Party Dress design concept, 2) to determine the results of the Combination of Living Yeast Ulos Fabric with Gorga Motif Written Batik on Gala Party Clothing. This type of research is experimental, with the subject of Alive Yeast Ulos Fabric with Gorga Motif Written Batik, Gala Party Dress. Observation method, collecting data by questionnaire and documentation. The research was carried out by creating 3 designs which manifested as 1 design for a gala party dress, then tested for validity with a research instrument in the form of applying design elements through a questionnaire. The data analysis technique was carried out using Descriptive Statistical Analysis. The results of this study were (1) The combination of Living Yeast Ulos Fabric with Gorga Motif Written Batik on Gala Party Clothing was successfully created through several stages (a) determining the theme and source of ideas, (b) making the design by applying design elements, (c) validating the design. (2) The embodiment of the gala party dress design. (3) Documentation of the results of the design and the results of the embodiment of the gala dress. The conclusion of the gala dress design that was made was assessed by the panelists, who strongly agreed and agreed, namely in the application of design elements to the results of the Combination of Living Yeast Ulos Fabric with Gorga Motif Written Batik on Gala Party Dresses